2021
DOI: 10.1016/s0140-6736(21)01124-7
|View full text |Cite
|
Sign up to set email alerts
|

Protection by vaccination of children against typhoid fever with a Vi-tetanus toxoid conjugate vaccine in urban Bangladesh: a cluster-randomised trial

Abstract: Summary Background Typhoid fever remains a major cause of morbidity and mortality in low-income and middle-income countries. Vi-tetanus toxoid conjugate vaccine (Vi-TT) is recommended by WHO for implementation in high-burden countries, but there is little evidence about its ability to protect against clinical typhoid in such settings. Methods We did a participant-masked and observer-masked cluster-randomised trial preceded by a safety pilot phase in an urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 28 publications
5
71
0
Order By: Relevance
“…A randomized clinical trial of Typbar TCV, in children between 9 months and 15 years of age in Nepal, showed an efficacy of 82% [ 20 ]. Similar results were observed in a cluster-randomized trial of Typbar TCV in Bangladesh, which showed an efficacy of 85% among infants and children aged 9 months to 16 years [ 21 ]. The study also found no serious vaccine-related adverse events.…”
Section: Vaccines To Tackle Typhoid Burden and Amrsupporting
confidence: 84%
“…A randomized clinical trial of Typbar TCV, in children between 9 months and 15 years of age in Nepal, showed an efficacy of 82% [ 20 ]. Similar results were observed in a cluster-randomized trial of Typbar TCV in Bangladesh, which showed an efficacy of 85% among infants and children aged 9 months to 16 years [ 21 ]. The study also found no serious vaccine-related adverse events.…”
Section: Vaccines To Tackle Typhoid Burden and Amrsupporting
confidence: 84%
“…In a similar age population, a recent cluster randomized clinical trial in Bangladesh showed similar protection provided by Vi-TT (85%; 95% CI 76-91). 25 During an emergent extensively drug-resistant (XDR) S. typhi outbreak in Hyderabad Pakistan, a population-based prospective cohort study estimated VE TF at 95% (95% CI 93-96). 26 However, in a similar design to our study in a peri-urban community of Karachi, in a matched case-control study following a Vi-TT mass immunisation campaign, the estimated VE was 72% (95% CI 34-88) among children six months to 15 years, which was closer to our results among children in Harare.…”
Section: Discussionmentioning
confidence: 99%
“…Similar vaccine efficacy was observed in Malawi, with an efficacy estimate of 80.7% (intention-to-treat population) and 83.7% (per protocol population) against blood culture-confirmed typhoid fever among children 9 months through 12 years of age, after 18 months of study follow-up ( Table 1 ) [ 21 ]. In a cluster-randomized trial in Dhaka, Bangladesh total effectiveness of TCV was 85% among vaccinated children aged 9 months to 15 years [ 22 ]. Importantly, total effectiveness remained high across age groups, including among children younger than 2 years of age, in whom total effectiveness was 81% [ 22 ].…”
Section: Tyvac Clinical Trialsmentioning
confidence: 99%
“…In a cluster-randomized trial in Dhaka, Bangladesh total effectiveness of TCV was 85% among vaccinated children aged 9 months to 15 years [ 22 ]. Importantly, total effectiveness remained high across age groups, including among children younger than 2 years of age, in whom total effectiveness was 81% [ 22 ]. High efficacy after a single dose, and the consistency of results in different settings and age groups, supports broad use of TCV ( Table 1 ).…”
Section: Tyvac Clinical Trialsmentioning
confidence: 99%